Factors Affecting Waiting Time for Outpatient Prescription Services at Pukesmas Betoambari Baubau City: Factors Affecting Waiting Time for Outpatient Prescription Services at Pukesmas Betoambari Baubau City - Ni’ma Meilani; Venny Alfreda Purwanti; Eky Endriana Amiruddin; Muh Subhan (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: Factors that can affect the waiting time are the number of prescriptions and the completeness of the prescription, the availability of human resources, the availability of drugs in accordance with the prescription, the standard operating procedures used. Objectives: The aims of this research is to determine the factors that influence the waiting time for outpatient prescription services at the Betoambari Health Center, Baubau City. Research Metodes: The research method used is analytic observational with a cross sectional study approach. The population of this study were all outpatients at the Betoambari Health Center. The number of samples is 358 respondents. The sampling technique used is Simple Random Sampling. The data analysis used was Univariate, Bivariate, and Multivariate Analysis. Results: The results of this study indicate that there is no effect of the number of prescriptions and prescription completeness with waiting time for prescription services (p value = 0.602 > = 0.25), there is an effect of availability of human resources with waiting time for prescription services (p value = 0.001 < = 0.25), and there is an effect of drug availability with waiting time for prescription services (p value = 0.153 < = 0.25). Conclusion: The conclusion of this study is that there is no influence between the number of prescriptions and the completeness of prescriptions, the availability of human resources, and the availability of drugs with the waiting time for prescription services. Keywords: drug prescription, outpatient, waiting time.